Predictive value of 18F-FDG PET/CT indices on extensive residual cancer burden in breast cancer patients treated with neoadjuvant chemotherapy [Valor predictivo de los índices 18F-FDG PET/TC sobre la carga tumoral residual en pacientes con cáncer de mama extenso tratadas con quimioterapia neoadyuvante] - KAYA, HANDAN; ŞAHİN ÖZKAN, HÜLYA; KÖSTEK, OSMAN; ARIKAN, RUKİYE; ÖZGÜVEN, SALİH; AKIN TELLİ, TUĞBA (Ediciones Doyma, S.L., 2021)
Aim: We investigated the correlation between 18F-FDG PET/CT indices and pathological response in breast cancer treated with neoadjuvant chemotherapy (NACT) which was scored with Residual Cancer Burden (RCB) system after surgery. Our aim is to detect extensive residual cancer burden earlier by using PET/CT indices. Methods: Characteristics of patients were retrieved retrospectively. Baseline maximum Standart Uptake Value (SUVmax), Metabolic Tumor Volume (MTV) and Total Lesion Glycolysis (TLG) indices and reduction rate (RR) between baseline and interim evaluation were calculated with FDG PET/CT scan. All patients were evaluated according to RCB scores after surgery. Pathological responses and PET/CT measurement results were analyzed with demographic and clinical parameters. Results: A total of 95 patients were included in the study. According to pathological responses, the distribution of RCB-0, -1, -2, -3 were 13 (13.7%), 11 (11.6%), 30 (31.6%), 41 (43.2%), respectively. Disease-free survival was significantly lower in the RCB-3 group compared to the pathological responder group (P=.01). According to multivariate analysis, RR of SUVmax was determined as an independent variable predicting extensive residual cancer burden with an optimal cut-off value of 86% (P<.05). Conclusions: We determined RR of SUVmax as an independent factor for predicting extensive residual tumor burden. We believe that RR of SUVmax is sufficient to predict pathological response in daily practice. In addition, MTV and TLG measurements do not contribute additionally to SUVmax alone and can cause unnecessary labor loss. © 2021
Keywords: Breast neoplasms; Drug therapy; Metabolic tumor volume; Positron emission tomography computed tomography; Residual cancer burden; Total lesion glycolysis